Synchrotron-based far-infrared spectroscopy of nickel tungstate - Kalinko, A.; Kuzmin, A.; Roy, P.; Evarestov, R.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Monoclinic antiferromagnetic NiWO4 was studied by far-infrared (30–600 cm−1) absorption spectroscopy inthe temperature range of 5–300 K using the synchrotron radiation from SOLEIL source. Two isomorphous CoWO4 and ZnWO4 tungstates were investigated for comparison. The phonon contributions in the far-infrared range of tungstates were interpreted using the first-principles spin-polarized linear combination of atomic orbital calculations. No contributions from magnetic excitations were found in NiWO4 and CoWO4 below their Néel temperatures down to 5 K.